Recognition Preference of Rhodamine Derivative Bearing Phthalimido Gly for Hg2+ by UV-Vis and Fluorescence Spectroscopy - Fanyong Yan; Meng Wang; Donglei Cao; Ning Yang; Bin Ma; Li Chen (Journal of Spectroscopy)
An effective Hg2+-specific probe 1 was designed and prepared based on Phthalimido Gly modified rhodamine B. The sensing behavior of probe 1 was studied by UV-Vis and fluorescence spectroscopy. Probe 1 showed excellent high selectivity and sensitivity towards Hg2+ over commonly coexistent metal ions in neutral solution, which could be attributed to the Hg2+-triggered ring opening of the spirolactam of the rhodamine moiety and the formation of a 1 : 1 1-Hg2+ complex. The limit of detection (LOD) based on 3δblank/k was calculated to be 2.8 × 10−8 M, as well as an excellent linear relationship with the concentration of Hg2+ in the range from 0.1 × 10−6 to 1.0 × 10−6 mol/L (R2=0.98927). In addition, the effects of pH, coexisting metal ions, and the reversibility were investigated in detail.